Lived experiences of parents of premature babies in the intensive care unit in a private hospital in Johannesburg, South Africa - Erika Steyn; Marie Poggenpoel; Chris Myburgh (AOSIS, 2017)
Background: Many of the 15 million premature babies born worldwide every year survive because of advanced medical interventions. Their parents have intense experiences when their babies are in the intensive care unit (ICU), and these have an impact on their thoughts, feelings and relationships, including their relationships with their premature babies. Objectives: The aim of the study was to explore and describe the lived experiences of parents of premature babies in an ICU. Method: Research design was qualitative, exploratory, descriptive and contextual. A purposive sample of parents with premature babies in an ICU in a private hospital in Johannesburg Gauteng in South Africa was used. Eight parents, four mothers and four fathers, married and either Afrikaans or English-speaking, were included in the study. Data were collected by conducting in-depth phenomenological interviews with them and making use of field notes. Trustworthiness was ensured by implementing the strategies of credibility, transferability, dependability and confirmability. Ethical principles such as autonomy, beneficence, nonmaleficence and justice were adhered to throughout the research process. Results: Thematic analyses were utilised to analyse the data. Two themes in the experiences of parents with premature babies in ICU became apparent. Parents experienced thoughts, emotions and hope while their premature babies were in the ICU as well as challenges in their relationships and these challenges influenced their experiences. Recommendations: Mindfulness of intensive care nurses should be facilitated so that intensive care nurses can promote the mental health of parents with premature babies in the ICU. Conclusion: Parents with premature babies in the ICU have thoughts and emotional experiences which include hope and they affect parents' relationships.